Changes in the state of paramagnetic centers and lattice parameter of micro-structured Si under the influence of weak magnetic field - Trachevsky, V.V.; Steblenko, L.P.; Demchenko, P.Y.; Koplak, O.V.; Kuryliuk, A.M.; Melnik, A.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
In this work, the influence of weak magnetic field on structure-dependent
properties of micro-structured Si was determined. The researches of EPR-spectra
inherent to micro-structured Si showed the presence of the spectral line at H ~ 3500 Oe
that appears from centers with the g-factor g ~ 2.0010 (Pв – centers). Intensity of the
determined spectral line decreases twice after magnetic processing. The observed redox
processes and evolution of defect structure are interpreted as the influence of magnetic
field on micro-structured Si. Calculations made using the data of X-ray diffractometric
researches showed an essential decrease of internal strains and respective increase of the
lattice parameter in micro-structured Si samples after magnetic processing in the weak
magnetic field.